Synthesis and characterization of biocompatible poly (L-lactide) using zinc (II) salen complex - Rade, Priyanka P.; Garnaik, Baijayantimala (International Journal of Polymer Analysis and Characterization, 2020)
A biocompatible zinc (II) complex based on a tetradentate N,N,O,O-type salen ligand was synthesized, characterized and used for the solvent-free ring-opening polymerization (ROP) of L-lactide in bulk at 180 degrees C to prepare high molecular weight poly(L-lactide) (M-n: 82,600 Da;M-w: 140,000 Da; PDI: 1.70). Poly(L-lactide) (PLLA) was characterized using FTIR,H-1 NMR,C-13 NMR, GPC, TGA, DSC, WAXD, and MALDI-ToF. Kinetic measurement was carried out and first-order behavior to monomer was observed. Thek(app)was found as 6 +/- 0.001 x 10(-4 )s(-1). The biocompatibility of the PLLA was confirmed byin vitrocytotoxicity against NIH/3T3 fibroblast cell line and can be used in biomedical applications.
Keywords: Biocompatible; Biomedical Applications; in vitro; PLLA; zinc (II) salen complex